Effectiveness of physical activity promotion based in primary care: systematic review and meta-analysis of randomised controlled trials. (26th March 2012) - Orrow, Gillian; Kinmonth, Ann-Louise; Sanderson, Simon; Sutton, Stephen
Abstract : Objectives To determine whether trials of physical activity promotion based in primary care show sustained effects on physical activity or fitness in sedentary adults, and whether exercise referral interventions are more effective than other interventions. Design Systematic review and meta-analysis of randomised controlled trials. Data sources Medline, CINAHL, PsycINFO, EMBASE, SPORTDiscus, Centre for Reviews and Dissemination, the Cochrane Library, and article reference lists. Review methods Review of randomised controlled trials of physical activity promotion in sedentary adults recruited in primary care, with minimum follow-up of 12 months, reporting physical activity or fitness (or both) as outcomes, and using intention to treat analyses. Two reviewers independently assessed studies for inclusion, appraised risk of bias, and extracted data. Pooled effect sizes were calculated using a random effects model. Results We included 15 trials (n=8745). Most interventions took place in primary care, included health professionals in delivery, and involved advice or counselling given face to face or by phone (or both) on multiple occasions. Only three trials investigated exercise referral. In 13 trials presenting self reported physical activity, we saw small to medium positive intervention effects at 12 months (odds ratio 1.42, 95% confidence interval 1.17 to 1.73; standardised mean difference 0.25, 0.11 to 0.38). The number needed to treat with an intervention for one additional sedentary adult to meet internationally recommended levels of activity at 12 months was 12 (7 to 33). In four trials reporting cardiorespiratory fitness, a medium positive effect at 12 months was non-significant (standardised mean difference 0.51, −0.18 to 1.20). Three trials of exercise referral found small non-significant effects on self reported physical activity at 12 months (odds ratio 1.38; 0.98 to 1.95; standardised mean difference 0.20, −0.21 to 0.61). Conclusions Promotion of physical activity to sedentary adults recruited in primary care significantly increases physical activity levels at 12 months, as measured by self report. We found insufficient evidence to recommend exercise referral schemes over advice or counselling interventions. Primary care commissioners should consider these findings while awaiting further trial evaluation of exercise referral schemes and other primary care interventions, with longer follow-up and use of objective measures of outcome.